1983
DOI: 10.1097/00132586-198308000-00041
|View full text |Cite
|
Sign up to set email alerts
|

I.M. or I.V. Atropine or Glycopyrrolate for the Prevention of Oculocardiac Reflex in Children Undergoing Squint Surgery

Abstract: The frequency and nature of the oculocardiac reflex and its prevention by atropine or giycopyrrolate (i.m. and l v) have been studied in 160 children undergoing surgery for the correction of squint. Ninety per cent of those given no anticholinergic premedication exhibited the reflex. This was decreased to about 50% in those receiving the drugs i.m. Giycopyrrolate 7.5ngkg~' and atropine 15ngkg~' i v. were effective in most instances, the latter being slightly better However, giycopyrrolate was associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 0 publications
4
41
0
Order By: Relevance
“…This is comparable with that evoked from the cornea, as described in the present study, and is similar to the so-called OCR observed during both ophthalmic surgery (5,12,14,23,32) and ophthalmic subconjunctival injections in conscious humans (23).…”
Section: Corneal-evoked Cardiorespiratory Responsessupporting
confidence: 92%
See 2 more Smart Citations
“…This is comparable with that evoked from the cornea, as described in the present study, and is similar to the so-called OCR observed during both ophthalmic surgery (5,12,14,23,32) and ophthalmic subconjunctival injections in conscious humans (23).…”
Section: Corneal-evoked Cardiorespiratory Responsessupporting
confidence: 92%
“…This pattern of response was common to all types of stimuli applied to the surface of the cornea, including chemical, mechanical, and electrical, and similar to that observed during ophthalmic surgery in humans (5,14,32), which can lead to cardiac arrest (12,23,24). Furthermore, the cardiac component of the corneal-evoked response was mediated, in part, by the NTS (7).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…It has been suggested that it is related to the oculocardiac reflex [13]. But the incidence of nausea is still high, even though this reflex can be inhibited by atropine or glycopyrrolate [2,14]. Another hypothesis is an oculo-emetic reflex arising from stress in the squint-corrected eye [15].…”
Section: Discussionmentioning
confidence: 99%
“…The prophylactic use of anticholinergic drugs may be hazardous in some patients having a history of tachycardia, hyperthyroidism, angle closure glaucoma and elderly patients with a history of coronary artery disease. In past, local anaesthesia was administered behind the eye as retrobulbar block was originally supposed to prevent the stimulation of OCR, but in later studies it was found to be one of the causative agents (26). Case studies involving deaths during emergency surgery are more in number as compared to elective surgery, and during high risk surgery than to low risk surgery as mortality rate increases with high risk and in emergency cases.…”
Section: Discussionmentioning
confidence: 99%